Elementary Teachers' Motivational Strategies: A Qualitative Analysis of Integrated Practices in Fourth-Grade Classrooms - Basira, Gusmiatni Dediyana; Wilade, Surahman; Rizal, Rizal; Isnayanti, Andi Nur (Papanda Publisher, 2025)
Learning motivation significantly influences elementary students' academic achievement, yet many teachers struggle to implement effective motivational strategies. This study analyzes teaching strategies employed to enhance fourth-grade students' learning motivation and identifies supporting and inhibiting factors in strategy implementation. A qualitative descriptive design was employed, with data collected through one-week systematic classroom observation, semi-structured interviews with the classroom teacher and school principal, and documentation review at SD Alkhairaat Tondo. Data were analyzed through reduction, display, and conclusion drawing processes. Six core motivational strategies were identified: (1) clear communication of learning objectives with ice-breaking activities, (2) association of content with students' daily lives, (3) implementation of varied and interactive teaching methods including technology integration, (4) consistent positive reinforcement through praise and tangible rewards, (5) personal approaches to individual students, and (6) joint evaluation with comprehensive reflection. Progressive increases in student engagement and participation were observed across the week. Supporting factors included adequate facilities, administrative support, professional development, and positive school culture, while inhibiting factors encompassed heterogeneous student motivation, time constraints, and varying confidence levels. Effective motivation enhancement requires comprehensive, integrated implementation of multiple evidence-based strategies. The findings validate convergence between teachers' intuitive practices and research-based motivation principles, offering practical models for educators and informing professional development approaches.